Mechanical Property Comparison of 23-, 25-, and 27-Gauge Trocars across Multiple Pressures and Vitrectomy Systems - James M. Lai, BS; Justin Chen, BS; Aaron J. Fils, BS; Landon J. Rohowetz, MD; William Herskowitz, BA; Heather Durkee, PhD; Cornelis Jan Rowaan, MS; Araliya N. Gunawardene, MS; Nimesh Patel, MD; Jean-Marie Parel, PhD; Nicolas A. Yannuzzi, MD (Ophthalmology Science)
Objective: To investigate the mechanical properties of 23-, 25-, and 27-gauge trocars when subjected to representative pressures of posterior segment surgery. Design: Experimental study. Subjects: There were no subjects included in this study. Methods: Twenty-four trocars each from Alcon, Dutch Ophthalmic Research Center (DORC), and Bausch & Lomb (B/L), distributed evenly across 23-, 25-, and 27-gauge sizes were included in this study. These trocars were tested at both 40 mmHg and 60 mmHg of pressure. Two failure end points were identified, and each trocar was tested until it reached both failure points. Main Outcome Measures: The number of instrument exchanges required before trocar valve failure at 2 predesignated end points. Results: A total of 72 measurements were made. Most notably between brands, 23-gauge Alcon trocars demonstrated significantly greater competence than their 23-gauge counterparts in B/L and DORC at both 40 mmHg and 60 mmHg pressures (P < 0.01). However, at the 25- and 27-gauge sizes, there were no significant differences in competence between trocar brands (P > 0.05). Conclusions: Based on the findings of this study, 23-gauge valved trocars from B/L and DORC exhibited a significantly lower threshold for compromise compared to that of Alcon valved trocars, likely attributable to differences in valve placement design. Surgeon experience, vitrector preference, and the specific type of surgery performed are important considerations in the choice of vitrector gauge and brand. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.